The gendered aspects of the austerity regime in Greece: 2010-2017 - Kosyfologou, Aliki (Berlin, 2018)
"Though austerity has prevailed across Europe to varying degrees, Greece in particular faces a situation of permanent austerity. The fiscal consolidation programs implemented since 2010 have brought extensive cuts to the public sector, over-taxation, privatizations, institutional reforms, devaluation of labour, high unemployment and precariousness. The social crisis provoked by fiscal austerity has also had major negative impacts on gender equality, undermining important employment and social welfare protections and putting gender equality policies on hold. Austerity halted progress towards gender equality, causing deeper gendered segregation in the labour market and a downward levelling of gender gaps in wages, working conditions and poverty. Νevertheless, racial and gender inequality reinforced in the context of the neoliberal regime are being taken up by the political agenda and discourse of the country’s large scale anti-austerity movement. New forms of political praxis and organizing have emerged in which women and youth occupy crucial political roles. In this context, a more intersectional approach and relation was promoted between the antifascist, antiracist, feminist, and LGBTQI movements. This study explores the gendered dimensions of the austerity regime in Greece, focusing on labour relations, political participation, interpersonal and interfamilial relations, care, gender-based violence, social and political rights. Moreover, it seeks to contribute to a transnational overview of austerity’s gender-related impacts in search of alternative strategies from a feminist perspective.'"